THE EFFECT OF SOCIAL MEDIA MARKETING ON MARKETING PERFORMANCE WITH SOCIAL MEDIA ADVERTISING, RELIABILITY, AND CUSTOMER ENGAGEMENT AS MEDIATING VARIABLES IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN THE FURNITURE INDUSTRY - Rokib; Ali; Sisno Riyoko (MANAJEMEN DEWANTARA, 2026)
The development of information technology, particularly social media, has drastically changed the marketing landscape, creating both challenges and opportunities for furniture craftsmen in Jepara. This study aims to analyze the effect of Social Media Marketing (SMM) on Marketing Performance with Social Media Ads, Reliability, and Customer Engagement as mediating variables. This explanatory quantitative study uses primary data from 125 furniture craftsmen selected through purposive sampling. The data were analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results show that Social Media Marketing does not have a significant direct effect on Marketing Performance. However, the effect becomes positive and significant when mediated by Social Media Ads, Reliability, and Customer Engagement. These findings indicate that to improve marketing performance (sales and market share), furniture craftsmen's social media strategies must be transformed through the use of targeted paid advertising, proof of business reliability to build trust, and active interaction with customers.